2018
DOI: 10.2214/ajr.17.18546
|View full text |Cite
|
Sign up to set email alerts
|

Image Quality of Prospectively ECG-Triggered Coronary CT Angiography in Heart Transplant Recipients

Abstract: Prospectively ECG-triggered coronary CTA examinations of HTx recipients yielded diagnostic image quality with low radiation dose. Coronary CTA is a promising noninvasive alternative to routine catheterization during follow-up of HTx recipients to diagnose CAV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…While in older scanners image quality depended strongly on the heart rate [29][30][31], recent studies have shown that contemporary CTA technology reaches diagnostic image quality [18,19,32,33]. Our study endorses these results by revealing good image quality at a mean heart rate of 74 bpm and median effective radiation dose of 5.8 mSv.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…While in older scanners image quality depended strongly on the heart rate [29][30][31], recent studies have shown that contemporary CTA technology reaches diagnostic image quality [18,19,32,33]. Our study endorses these results by revealing good image quality at a mean heart rate of 74 bpm and median effective radiation dose of 5.8 mSv.…”
Section: Discussionsupporting
confidence: 84%
“…Coronary computed tomography angiography (CTA) represents a noninvasive alternative to ICA and IVUS [10][11][12] and has been successfully used in numerous large trials investigating coronary heart disease (CHD) [13][14][15][16] and in smaller studies of CAV [17][18][19]. Still, it remains unknown whether quantitative CTA measures are associated with CAV and how the diagnosis of CAV using these measures agrees with diagnosis made by ICA.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the clinical implementation of CCTA as a first-line image modality for the detection of CAV has been hampered due to lower image quality and higher radiation dose in patients with elevated heart rates [3]. Recent studies have shown that contemporary CT technology reaches good diagnostic image quality in HTx patients at reasonable radiation exposure [6,7,11,12]. In the present study with a large realworld HTx population with relatively high heart rates, similar results were observed.…”
Section: Feasibility Of Ccta For the Detection Of Cavsupporting
confidence: 84%
“…CCTA visualizes both the coronary lumen and wall with high sensitivity (86% to 89%) and specificity (89% to 99%), but has not yet been widely adopted due to concerns about potential lower image quality and higher radiation dose associated with the relatively high heart rates often encountered in HTx patients [5]. However, technical advances including increased detectorrow coverage, decreased rotation time, and iterative reconstruction algorithms have improved the image quality of CCTA in patients with elevated heart rates [6,7]. Therefore, CCTA has become a more attractive alternative to ICA for the detection of CAV with more ease for the patient and logistics at a lower cost and could be used as gatekeeper to ICA.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the denervation of the transplanted heart, which leads to an absence of heart-rate variation. Further studies have confirmed that a regular heart rate is associated with better image quality [48,49].…”
Section: The Role Of Coronary Computed Tomography Angiography and Nuc...mentioning
confidence: 86%